2016
DOI: 10.1038/srep23926
|View full text |Cite
|
Sign up to set email alerts
|

Controlling superconducting spin flow with spin-flip immunity using a single homogeneous ferromagnet

Abstract: Spin transport via electrons is typically plagued by Joule heating and short decay lengths due to spin-flip scattering. It is known that dissipationless spin currents can arise when using conventional superconducting contacts, yet this has only been experimentally demonstrated when using intricate magnetically inhomogeneous multilayers, or in extreme cases such as half-metals with interfacial magnetic disorder. Moreover, it is unknown how such spin supercurrents decay in the presence of spin-flip scattering. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 46 publications
4
65
0
Order By: Relevance
“…Therefore, it would be desirable to identify a setup where the LRTs can be tuned with a sole in-plane variation of the magnetization to minimize the stray field effect on the superconductor itself. This would be a different result than previous works [13,14,[16][17][18][19][20] that have considered how to control the supercurrent via magnetization in Josephson contacts with spin-orbit coupling. A long-ranged supercurrent was predicted in Ref.…”
Section: Introductionmentioning
confidence: 61%
“…Therefore, it would be desirable to identify a setup where the LRTs can be tuned with a sole in-plane variation of the magnetization to minimize the stray field effect on the superconductor itself. This would be a different result than previous works [13,14,[16][17][18][19][20] that have considered how to control the supercurrent via magnetization in Josephson contacts with spin-orbit coupling. A long-ranged supercurrent was predicted in Ref.…”
Section: Introductionmentioning
confidence: 61%
“…An interesting expansion of the present work would be to explore how magnetic interfaces232425 and spin-orbit coupling would influence the proximity-gap phase diagram and topological properties of multiterminal Josephson junctions, as recent works have demonstrated that in particular the latter of these can induce several novel effects in both diffusive and ballistic superconducting hybrids13262728293031323334.…”
Section: Resultsmentioning
confidence: 99%
“…Spin-orbit fields can even induce superconducting proximity effects in half metals [31]. Moreover, magnetic anisotropies of the critical current with respect to the orientation of the present spin-orbit fields have been predicted to occur in lateral S/nanowire/S Josephson junctions with a Zeeman splitting [41][42][43], as well as in diffusive vertical S/F/S Josephson junctions [44].…”
Section: Introductionmentioning
confidence: 99%